Serum semaphorin 7A is associated with the risk of acute atherothrombotic stroke. Issue 4 (7th February 2019) - You, Tao; Zhu, Zhengbao; Zheng, Xiaowei; Zeng, Nimei; Hu, Shuhong; Liu, Yifei; Ren, Lijie; Lu, Qiongyu; Tang, Chaojun; Ruan, Changgeng; Zhang, Yonghong; Zhu, Li
Abstract: Semaphorin 7A (Sema7A), a neural guidance cue, was recently identified to regulate atherosclerosis in mice. However, the clinical relevance of Sema7A with atherosclerotic diseases remains unknown. The aim of this study was to investigate the association between serum Sema7A and the risk of acute atherothrombotic stroke (AAS). We measured serum concentrations of Sema7A in 105 newly onset AAS cases and 105 age‐ and sex‐matched controls, showing that median Sema7A level in AAS cases was over three times of that in controls (5.86 vs 1.66 ng/mL). Adjusted for hypertension, body mass index, fasting blood glucose, total cholesterol, triglyceride, high‐density lipoprotein (HDL)‐cholesterol, low‐density lipoprotein (LDL)‐cholesterol, current smoking and alcohol consumption, multivariate logistic regression showed that higher Sema7A was independently associated with the odds of AAS (OR = 6.40, 95% CI: 2.88‐14.25). Each 1‐standard deviation increase in Sema7A was associated with a threefold higher odds of AAS (OR = 3.42, 95% CI: 1.84‐6.35). Importantly, adding Sema7A to a multivariate logistic model containing conventional cardiovascular risk factors improved the area under receiver operating characteristic curves from 0.831 to 0.891 for the association with AAS. In conclusion, elevated serum Sema7A is independently associated with the risk of AAS, suggesting that it may play a potential role in AAS.